The Politics of Displays: Science and Technology Exhibitions in Cold War Japan. - Kim, Yusung (Asian Studies Review, 2025)
This article investigates how science and technology, especially nuclear energy and space travel, materialised as concrete things and were embedded into everyday life through exhibitions and three-dimensional experiences in Japan during the cold war. In the historical and geopolitical context of Japan in the late 1950s and 1960s, the United States (US)–Japan alliance required that American propaganda agencies such as the US Information Service (USIS) in Japan operate effectively. To this end, science and technology were embodied as specific materials by being reproduced and circulated as tactile objects through exhibitions and displayable models, which formed a desirable environment that involved not only aesthetically attractive designs but also the implicative meanings of the geopolitical dynamics of the time. In particular, the article scrutinises how several exhibitions displayed new materiality in the form of miniatures and models under a newly proposed and constructed techno-environment. It does so by analysing records of exhibitions, expositions, and three-dimensional models that were displayed in Japan in the late 1950s and 1960s.